2007
DOI: 10.1016/j.febslet.2007.02.049
|View full text |Cite
|
Sign up to set email alerts
|

STAT1 regulates p73‐mediated Bax gene expression

Abstract: Although signal transducer and activator of transcription 1 (STAT1) mediated regulation of p53 transcription and apoptosis has been previously reported, modulation of other members of the p53 family of transcription factors remains poorly understood. In this study, we found that STAT1 and TA-p73 can interact directly and that p73-mediated Bax promoter activity was observed to be reduced by STAT1 expression in a p53-independent manner for which STAT1 Tyrosine-701 and Serine-727 are key residues. This study pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 58 publications
0
25
0
Order By: Relevance
“…Previous studies have shown that STAT1 cooperates with p53 to induce apoptosis by selectively enhancing the transcriptional activity of p53 on p53 target gene promoters bearing an ASPP2 signature, such as Bax (31) and Noxa (32). Because LPS-induced STAT1 activity induces ASPP2 expression, we tested whether LPS-induced nuclear ASPP2 and p53 may play a proapoptotic role in response to inflammatory stimuli.…”
Section: Lps Induces Nuclear Aspp2 Expression In a Mouse Model Of Matmentioning
confidence: 99%
“…Previous studies have shown that STAT1 cooperates with p53 to induce apoptosis by selectively enhancing the transcriptional activity of p53 on p53 target gene promoters bearing an ASPP2 signature, such as Bax (31) and Noxa (32). Because LPS-induced STAT1 activity induces ASPP2 expression, we tested whether LPS-induced nuclear ASPP2 and p53 may play a proapoptotic role in response to inflammatory stimuli.…”
Section: Lps Induces Nuclear Aspp2 Expression In a Mouse Model Of Matmentioning
confidence: 99%
“…Following transfection, cleared supernatents were prepared, assayed and analysed by Western blotting as outlined previously. 64 Statistical analysis. Luciferase data was analysed using Microsoft Excel (Microsoft) to determine the standard error around the mean, before the results were translated to fold activation of relative light units over basal control experiments.…”
Section: Methodsmentioning
confidence: 99%
“…Transfected or non-transfected mammalian cells were treated exactly as outlined previously. 64 In vitro kinase assays GST fusion proteins. Purified GST fusion proteins (immobilised on sepharose) were incubated in 1 ml of PLK kinase buffer (lacking ATP) for 5 minutes on ice after which they were harvested by centrifugation at 400 g for 20 seconds, all of the liquid phase removed and discarded.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations